Comments on the paper “How to calculate crystallite size from x-ray diffraction (XRD) using Scherrer method” by Siti Fatimah et al. published in ASEAN Journal of Science and Engineering 2 (2022) 65 - Tomaszewski, Paweł E. (Universitas Pendidikan Indonesia (UPI), 2023)
My comments concern the error in the crystallographic analyses presented in the commented paper “How to calculate crystallite size from x-ray diffraction (XRD) using Scherrer method” by Siti Fatimah et al. published in ASEAN Journal of Science and Engineering 2 (2022) 65.